Nutrients Regulate the Effects of Arbuscular Mycorrhizal Fungi on the Growth and Reproduction of Cherry Tomato - Wang, Lei; Chen, Xin; Du, Yeqin; Zhang, Di; Tang, Zhanhui (Frontiers in Microbiology, 2022)
Arbuscular mycorrhizal fungi (AMF) colonize the rhizosphere of plants and form symbionts with plants. Mycorrhizal symbionts have diversified ecological roles and functions which are affected by soil conditions. Understanding the effects of different AMF inoculation treatments on plants under varied nutritional conditions is of great significance for further understanding the effects of external environment regulating mycorrhizal symbiosis on plant phenotypic traits. In this study, the effects of four AMF inoculation treatments on the growth and reproductive performance of cherry tomato (Solanum lycopersicum var. cerasiforme) were investigated under three nutrient levels by pot experiment. It was found that the growth promoting effect of AMF on cherry tomato decreased with nutrient reduction, and the effects of the same AMF inoculation treatment on cherry tomato were different at different nutrient levels. Nutrient levels and AMF had interactive effects on flower characteristics, fruit yield, resource allocation and seed germination of cherry tomato. In addition, AMF could promote sexual reproductive investment. Nutrient levels and AMF also affected the accumulation of nitrogen and phosphorus in cherry tomato, and there were significant differences among different AMF inoculation treatments. The results indicated that nutrient differences could affect the symbiosis between AMF and plants, and confirmed that there were differences in the effects of the four AMF inoculation treatments on the growth and reproductive traits of plants. The differences of growth and reproduction characteristics of cherry tomato between different AMF inoculation treatments at different nutrient levels indicated that AMF symbionts had different effects on the growth and reproduction of cherry tomato under different nutrient conditions.